2005
DOI: 10.1212/01.wnl.0000162052.13838.b2
|View full text |Cite
|
Sign up to set email alerts
|

Nested polymerase chain reaction for assessing the clinical course of tuberculous meningitis

Abstract: The authors examined the usefulness of nested PCR (N-PCR) to detect Mycobacterium tuberculosis (MTB) DNA in CSF for assessing the clinical course of tuberculous meningitis (TBM). N-PCR successfully detected MTB DNA in all nine CSF samples from patients with suspected TBM. During anti-tuberculosis treatments, N-PCR results converted from positive to negative, correlating with the improvement of the patient's clinical condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 7 publications
4
53
0
4
Order By: Relevance
“…This study, similar to other studies, showed elevated serum ADA levels in pulmonary TB patients compared to those in normal individuals (7,11,(15)(16)(17)(18)(19)(20)(21)(22)(23); however, ADA level was not found to be a reliable indicator for differentiating between pulmonary TB and other pulmonary infections.…”
Section: Nosupporting
confidence: 89%
See 1 more Smart Citation
“…This study, similar to other studies, showed elevated serum ADA levels in pulmonary TB patients compared to those in normal individuals (7,11,(15)(16)(17)(18)(19)(20)(21)(22)(23); however, ADA level was not found to be a reliable indicator for differentiating between pulmonary TB and other pulmonary infections.…”
Section: Nosupporting
confidence: 89%
“…In the study that performed by Atalas in 2003, their results suggest that ADA level in pulmonary TB patients is higher than normal population, additionally the ADA levels in patients with tuberculosis pleurisy was higher than patients with other tuberculosis manifestations (15,18).…”
Section: Nomentioning
confidence: 93%
“…In the diagnosis of TBM, PCR has been widely used to detect M. tuberculosis DNA in CSF samples as a more rapid, sensitive and specific diagnostic method as compared to the conventional procedures involving acid-fast microscopy and isolation by culture [15]. Although few reports have shown that PCR for TBM is less sensitive than culture, its rapidity helps to ensure timely diagnosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…A recent example of this method includes the use of an IS6110 uniplex PCR assay that had 98% sensitivity (NPV, 99%) and a specificity of 100% (PPV ϭ 100%) against the "gold standard" of culture (167) and an overall sensitivity of 76.4% (NPV, 59.9%) and specificity of 89.2% (PPV, 94.7%) when clinical TBM was included (166). Several methods of PCR have been evaluated, including quantitative nested real-time PCR (208)(209)(210), the Amplicor Mycobacterium tuberculosis Test (23,24), and a variety of other in-house PCR assays (45,46,51,83,104,111,120,123,138,141,165,189,193). These assays have been evaluated specifically in HIV-coinfected patients (59,180) and also as a means to monitor therapy (180,210).…”
Section: Molecular and Biochemical Analysismentioning
confidence: 99%